2013
DOI: 10.1002/cam4.90
|View full text |Cite
|
Sign up to set email alerts
|

Absent/weak CD44 intensity and positive human papillomavirus (HPV) status in oropharyngeal squamous cell carcinoma indicates a very high survival

Abstract: Patients with human papillomavirus DNA positive (HPVDNA+) oropharyngeal squamous cell carcinoma (OSCC) have better clinical outcome than those with HPV DNA negative (HPVDNA−) OSCC upon intensive oncological treatment. All HPVDNA+ OSCC patients may not require intensive treatment, however, but before potentially deintensifying treatment, additional predictive markers are needed. Here, we examined HPV, p16INK4a, and CD44 in OSCC in correlation to clinical outcome. Pretreatment tumors from 290 OSCC patients, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 31 publications
4
47
0
Order By: Relevance
“…Among of tumors with viral cytopathic effect found in our series, we observed a predominant expression of CD44 and the phenotype CD44+/LeY-. Recently, Näsman et al observed in 290 oropharyngeal squamous cell carcinoma patients a poor DFS when the tumors had HPV+ and medium/strong CD44 intensity staining [38]. Also, Hufbauer et al showed in a cutaneous keratinocyte line PM1 that the expose to HVP lead to a shift of the total population from low toward higher CD44 cell surface expression and, in turn, pointed to a reduction in the number of terminally differentiated cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…Among of tumors with viral cytopathic effect found in our series, we observed a predominant expression of CD44 and the phenotype CD44+/LeY-. Recently, Näsman et al observed in 290 oropharyngeal squamous cell carcinoma patients a poor DFS when the tumors had HPV+ and medium/strong CD44 intensity staining [38]. Also, Hufbauer et al showed in a cutaneous keratinocyte line PM1 that the expose to HVP lead to a shift of the total population from low toward higher CD44 cell surface expression and, in turn, pointed to a reduction in the number of terminally differentiated cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…LGII-intensity were coded as 0 if 'absent'; 1 if 'weak'; 2 if 'normal' and 3 if 'strong' [16,17]. Stage was coded as 0 if stage was I or II; 1 if stage was III; 2 if stage was IVa; 3 if stage was IVb; and 4 if stage was IVc.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected on patients diagnosed during 2000-2011 with HPV DNA positive tumour biopsies, 308 with TSCC (ICD-10 code C09.0-9) and 112 with BOTSCC (ICD-10 code C01.9), at Karolinska University Hospital [5,[16][17][18][19][20][21]. Radiotherapy (RT) was given up to 68 Gy in conventional or accelerated settings, with or without induction chemo-RT (CRT) (Cisplatin + 5FU with/without Docetaxel, or with/without Capecitabine).…”
Section: Patients Tumours and Study Designmentioning
confidence: 99%
See 2 more Smart Citations